LEXICAL DESYNONYMY IN B. VIAN’S NOVEL “FROTH ON THE DAYDREAM” - Anastasiia V. Lepetiukha (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2024)
The article is dedicated to the studies of lexical desynonyms that are formed and transformed in the space of the operating time of the mental kineticism by means of cognitive polyoperations (psychomechanisms) during the first formal seizure by the thought of its movement in two stages: 1) phenomenological construction of the being and its structures and categories by the addresser as a result of which is formed the lexical primary structure having as basis “sublinguistic schemes”, typical models used to construct different simple and complex linguistic signs; 2) creation of simple secondary desynonymic linguistic signs from which the speaker chooses the co(n)textually (linguistically and/or situationally) pertinent structure. They are actualized in the form of ludic preferential options, according to the communicative intention to facilitate or to complicate the interpretation of the information to the receiver or to the author’s idiostyle, which are characterized by the asymmetry of semasiological and denotative meanings in the language and in the discourse at intrasign and intersigns levels. The goal of the article is to identify the processes of the formation and actualization of asymmetrical desynonymic signs, to identify the types of lexical desynonyms in B. Vian novel “Froth on the Daydream” and to justify their co(n)textual pertinence depending on the communicative intention and the idiostylistic features of the writer. In this research, we use the transformational method, which makes possible the identification of structural and semantic peculiarities of primary and secondary desynonymic constructions as asymmetrical signs in language and discourse, the method of systematization which helps to establish the typology of lexical desynonyms in the novel “Froth on the Daydream” by B. Vian and the linguo-stylistic and interpretative analyzes in order to reveal and characterize the idiostylistic features of the author and to justify the co(n)textual pertinence of the distinguished lexical desynonyms. In the process of analysis of the novel “Froth on the Daydream” by B. Vian, they revealed reduced, extended and quantitatively equacomponential desynonyms phonologically resembling or phonically identical to the primary structure, the derivative desynonyms, the preferential options with the surimpression and with a new semantic co(n)textual meaning in order to precise the author’s idea, to accentuate a qualifier of an object or a character, to transmit the supplementary information on аn exteriorized referent to the reader. All the distinguished types of lexical desynonyms perform the intra- and interphrasal stylistic‑expressive function reflecting the author’s individual vision of the objective reality. It is concluded that desynonymic lexical units represent biunambiguous emphatically accentuated linguo-discursive signs constructed and transformed in the space of the operating time of the causation of the linguo-discursive act which are not stabilized in use being substitutable in a particular co(n)text serving to enrich the intra- and interphrasal content by means of complementary co(n)textual semantic nuances facilitating or complicating the identification of desynonymized referents to the receiver.